OPTIMALISASI PROSES PRODUKSI YANG MELIBATKAN BEBERAPA FAKTOR DENGAN LEVEL YANG BERBEDA MENGGUNAKAN METODE TAGUCHI - Annisa Intan Mayasari; Triastuti Wuryandari; Abdul Hoyyi (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2014)
Taguchi method is a method that purposes to improve the quality of products and processes at the same time with the purpose of reducing costs and resources to a minimum. Taguchi method is one example of a fractional factorial design that uses orthogonal arrays to reduce the number of experiments. The analytical tool used was ANOVA and Signal to Noise Ratio. ANOVA was used to determine the factors that affect the response and Signal to Noise Ratio are used to determine the combination of factors that affect the performance of the product so that the resulting optimal response. Based on the results of tests performed to determine the factors that influence the design of electronic circuits that will produce the center frequency of 35.75 megahertz at a temperature of -10 ℃, the significant factor is the factor A, B, C, D, F, and H. The best combination is obtained A2, B2, C2, D3, F2, dan H3. Factor F has the greatest percent contribution is 42.57%, the next factor D, H, C, A, and B, respectively 8.83%, 7.37%, 5.93%, 3.90% and 3.84%.